Analysis of Students' Ability in Mastering the Process Components of Using Symbolic, Formal and Technical Language and Operation and Representation of PISA Mathematical Literacy at SMPN 4 Bengkulu City - Stiadi, Elwan (Universitas Bengkulu, 2025)
This study aims to analyze students' abilities in mastering the process components of PISA mathematical literacy. This research is classified as descriptive research. The subjects of this study were students from classes IX-1 and IX-2 at SMP Negeri 4 Kota Bengkulu during the odd semester of the 2021/2022 academic year. The instruments and data collection techniques used in this research were test sheets and interviews. The results of the study show that 45.45% of students demonstrated the ability in the representation process, while 40.74% of students demonstrated the ability in the use of symbolic, formal, and technical language and operations process when solving PISA 2012 mathematical literacy problems.